Model Hubungan Antar Pemangku Kepentingan dalam Koordinasi Penanganan Bencana di Kota Padang - Dicky Fatrias; Ringga Sri Rahayu Agustia (Jurnal Optimasi Sistem Industri, 2019)
Padang, capital of West Sumatera, is one of a disaster-prone area in Indonesia which was impacted the most by 2009 earthquake disaster. After seven years passed, The Regional disaster management agency of West Sumatra stated that the coordination between relevant government agencies in disaster management was still lacking. Associated with such issue, this research proposes to model an appropriate stakeholder’s coordination scheme based on the concept of 3PR (public, private, and people relationship). After all candidates of stakeholder are considered, a successful indicators of disaster response are identified. Using fuzzy AHP, the indicators were weighted based on their relative importance, and the traffic light system was applied to screen the weighted indicators. Finally, the role of each stakeholder was then identified and charted using the interpretive structural model (ISM). The proposed relationship model in disaster management coordination in Padang City consists of two levels. The first level consists of five stakeholders, namely Semen Padang, Insurance, Muhammadiyah, LPP TVRI, and Andalas University. The second level consists of three stakeholders, namely BPBD Kota Padang, Padang City Social Service and Padang City Health Office. Based on the above mapping, public sectors hold the biggest responsibility in the coordination of disaster management while the private sector and people as a supporter in the success of disaster management activities in the city of Padang